Determinants of Financial Performance: The Role of Financial Statement Completeness, Liquidity, and Profitability in Listed Retail Firms on the Indonesia Stock Exchange - Lokananta Puspa Indrian; Taufiq Andre Setiyono (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2026)
Purpose: This research aims to explore how the completeness of financial statements, liquidity ratio, and profitability influence the financial result of retail firms listed on the Indonesia Stock Exchange. Method: A quantitative methodology is utilized, relying on secondary data sourced from annual financial statements from 2022 to 2024. The study includes a sample of 30 retail firms chosen through purposive sampling, amounting to 90 observations. Financial performance is evaluated through Return on Assets, the completeness of financial statements is measured with a completeness index in accordance with PSAK No. 1, liquidity is represented by the Current Ratio, and profitability is assessed via the Net Profit Margin. The data analysis employs multiple linear regression using SPSS. Findings: The findings reveal that completeness of financial statements and liquidity ratio have a negative and non-significant impact on financial performance, whereas profitability demonstrates a positive and significant influence. Collectively, all independent variables have a significant effect on financial performance. Implications: The results suggest that profitability server as the primary factor determining financial performance in retail businesses, while the completeness of financial statements and liquidity support this relationship.